Study of Optical Properties and Calculation of the Energy Gap for LINAWO4 Compound - Moftah Ben Yazid; Moufida Krimi; Abdallah Ben Rhaiem; Amjad Elhams; Ahmed Awhida (African Journal of Advanced Pure and Applied Sciences, 2024)
In this study, the solid-state method was employed for the synthesis of the chemical compound LiNaWO4. According to X-ray diffraction (XRD) analysis, it was found to crystallize in a triclinic crystal system with the parameters of the lattice (a = 12.82 Å, b = 17.49 Å, c = 7.25 Å, α = β = γ= 90°) and the P222 space group. Scanning electron microscopy (SEM) analysis revealed that the compound possesses a compact structure with some porosity. Furthermore, (UV-Vis) spectroscopy was utilized to investigate the optical properties of our compound. The study demonstrated the presence of an energy gap of 4.2 eV, confirming that this compound is a semiconductor material. The Urbach energy was discovered to be approximately 0.38 eV